Cine littera: um festival dionisíaco na construção de uma pedagogia do olhar na sala de aula - Carvalho, Hêlena Paula Domingos de (2021)
The research investigates the insertion of the Cinema in the formative process of High School students of a public vocational school specialized in Agriculture, in the city of Foz do Iguaçu, Paraná, situated in a trinational border between Brasil, Argentina and Paraguay. The intention is to present Cinema as an epistemologic source and contribution to teaching, through means of teaching pedagogic mediation in an interdisciplinary reading. Considering that, the critical-philosophical content of a movie is processed through the images that have an emotional enlightening effect. Therefore, problematizes the viewing with more acuity, to the perception of how the images affect, sensibilize and pervade the cognizant action. Consequently, inquires: How the Cinema in the classroom enables the development of the pedagogy of the sight? It features for the investigation, an empirical project through means of action-research. The general objective of this thesis centers in investigating how the Cinema enables to ressignify the learningship through means of the pedagogy of the sight. The research is grounded to the axiological fundamentals of the Cultural Studies, which comprehend the culture as a field of fight around the social signification. It is based, yet, on the theorists that insert the image and the cinema in the frames of referentials of the post-critical theories mediated by the philosophy of the difference. The impressions, reflexions and voices resultant of the empirical research with students of basic education, allows to argument that is possible to read the image in a critical form, in a theoretical-methodological construction which involves the pedagogy of the sight with the Cinema in the classroom. The research, observes that the philosophical exercise is better understood under the light of reason and affection, since, not everything is utterable – but, expressible by the image and the pedagogy is the articulator of this possibility in the process of teaching and learningship.